Effects of priming exercise on the oxygen uptake kinetics and muscle fatigue during high-intensity cycling - Salvador, Paulo Cesar do Nascimento (2018)
Tese (doutorado) - Universidade Federal de Santa Catarina, Centro de Desportos, Programa de Pós-Graduação em Educação Física, Florianópolis, 2018.